Engineering interactive design using internet application (phase 1) / Rozaidi Shaarip, Tengku Ahmad Rashidi Tengku Nordin and Muhammad Asrul Zulkipli - Shaarip, Rozaidi; Tengku Nordin, Tengku Ahmad Rashidi; Zulkipli, Muhammad Asrul (1997)
This project, Engineering Interactive Design Using Internet (phase 1) is basically a introduction to the engineering students to the world of programming and publishing the program through the Internet. We are using Java WorkShop as a software to build an interactive program. The program that we had produced is a basic interactive design where users can draw ovals. It is a kind like Auto CAD but it's much more simpler. Our program can be access through the Internet only because we made this program to use by the Internet surfers around the world. Not only that, we are also introduces tlie way how to make a Web page and publish it through the Internet. So, to the Internet surfers that only surfs through the Internet, try make your own page.